ANALISIS KOMUNIKASI ANTARETNISDI KALANGAN PEMUDA NUSANTARA DALAM MEMBANGUN SPIRIT NASIONALISME MENUJU KERJA SAMA ANTARBANGSA MELALUI INDONESIA – KOREA YOUTH EXCHANGE PROGRAM (IKYEP) - Rizky Maulidiana Haris; Hafied Cangara; Muhammad Iqbal Sultan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2015)
Abstract The purpose of this research is to investigate the ways to develop the nationalist spirit in the interethnic communication among Nusantara youth towards the international cooperation through IKYEP, to investigate the interethnic communication among Nusantara youth in cultivating the Indonesian nationalistic spirit towards the international cooperation and to investigate the application form of the nationalistic spirit in the interethnic communication among Nusantara youth towards the international cooperation through IKYEP. The method used was a descriptive research method with the qualitative approach through direct observation on the research objects and interviews. The data were then analyzed using Miles and Huberman interactive model. The results revealed that as the first step, the Facebook group was formed which would function to build up the nationalistic spirit at the early stage. PDT phase contained the activities which mentally supplied the participants with group bounding and team work. The interethnic communication which occured were in the forms of culture, faith systems, stereotypes, ethnocentrism and the short duration of the program. The spirit of nationalism had grown in the interethnic communication as the results achieved in the form of positive discourse, self reflection to respect the cultural differences. Besides, there was the feeling of responsibility to carry out their tasks. The application forms were the tolerance value, solidarity, integrity, commitment, and cooperativeness.AbstrakTujuan penelitian ini untuk mengetahui cara membangun spirit nasionalisme dalam komunikasi antaretnis di kalangan pemuda nusantara menuju kerja sama antarbangsa melalui IKYEP, untuk mengetahui komunikasi antaretnis di kalangan pemuda nusantara dalam menumbuhkan spirit nasionalisme Indonesia menuju kerja sama antarbangsa dan untuk mengetahui bentuk penerapan spirit nasionalisme dalam komunikasi antaretnis di kalangan pemuda nusantara menuju kerja sama antarbangsa melalui IKYEP. Metode yang digunakan adalah metode penelitian deskriptif dengan pendekatan kualitatif melalui pengamatan langsung terhadap objek penelitian dan wawancara. Kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa sebagai langkah awal dibuat group Facebook yang berfungsi untuk membangun spirit nasionalisme. Fase PDT berisi kegiatan yang membekali dari segi mental, group bounding dan team work. Komunikasi antaretnis berupa kebudayaan, sistem kepercayaan, stereotip, etnosentrisme serta durasi program yang singkat. Spirit nasionalisme tumbuh sebagai hasil yang dicapai berupa wacana positif, refleksi diri untuk menghormati perbedaan kebudayaan serta tanggung jawab untuk menjalankan tugas. Bentuk penerapan berupa nilai toleransi, solidaritas, integritas, komitmen, dan kebersamaan.